The first record of Ligophorus Euzet & Suriano, 1977 (Monogenea: Dactylogyridae) on Crenimugil buchanani (Teleostei: Muglidae) from Thailand based on morphological and molecular analyses. Issue 6 (20th September 2018) - Pakdee, W.; Ogawa, K.; Pornruseetriratn, S.; Thaenkham, U.; Yeemin, T.
Abstract: Ligophorus satunensis n. sp. was collected from the bluetail mullet, Crenimugil buchanani (Bleeker, 1853), caught off Satun, Thailand, representing the first report of the Ligophorus species in Thailand. The new species is most similar to Ligophorus fenestrum Soo & Lim, 2012 in its fenestrated dorsal hamuli, a ventral bar with a long, bifurcated anteromedian protuberance (AMP) without lateral pieces, and a non-sclerotized vagina. However, it differs from the latter in its dorsal hamuli (up to two layers of fenestrations of the dorsal hamuli in L. satunensis n. sp. vs six layers in L. fenestrum ), ventral hamuli (nonfenestrated vs fenestrated), penis (turning a full circle before reaching the genital pore vs turning less than half a circle), and its accessory piece (non-grooved basally and grooved distally vs simply grooved along its entire length). A single specimen, very similar to L. satunensis n. sp., obtained from the same host fish, which can be differentiated from the latter by a considerably shorter AMP of the ventral bar and a smaller and slender dorsal hamuli, is tentatively designated here as Ligophorus sp. Moreover, the phylogenetic trees constructed from the concatenated sequences of partial large-subunit nuclear ribosomal DNA (28S) and nuclear ribosomal internal transcribed spacer 1 (ITS1) regions support that L. satunensis n. sp. is a new species closely related to L. fenestrum .